2017
DOI: 10.1128/aem.02737-16
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Composition and Threshold Concentration for Growth of Legionella pneumophila on Surfaces Exposed to Flowing Warm Tap Water without Disinfectant

Abstract: Legionella pneumophila in potable water installations poses a potential health risk, but quantitative information about its replication in biofilms in relation to water quality is scarce. Therefore, biofilm formation on the surfaces of glass and chlorinated polyvinyl chloride (CPVC) in contact with tap water at 34 to 39°C was investigated under controlled hydraulic conditions in a model system inoculated with biofilm-grown L. pneumophila. The biofilm on glass (average steady-state concentration, 23 Ϯ 9 pg ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 70 publications
6
49
0
Order By: Relevance
“…The logarithmic means of the LpCs did not correlate with the BFPs on glass and CPVC (Table 3). However, in the biofilms exposed to samples from SSFs I and III, the high LpC values with high CFU/pg ATP ratios fitted with the relationship (solid line) derived in a previous study (9). The LpC/BfC ratios of a number of colony counts in the biofilms exposed to samples from SSFs II and IVD exceeded the relationship presented by the solid line ( Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The logarithmic means of the LpCs did not correlate with the BFPs on glass and CPVC (Table 3). However, in the biofilms exposed to samples from SSFs I and III, the high LpC values with high CFU/pg ATP ratios fitted with the relationship (solid line) derived in a previous study (9). The LpC/BfC ratios of a number of colony counts in the biofilms exposed to samples from SSFs II and IVD exceeded the relationship presented by the solid line ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…In 1986, the Health Council of the Netherlands recommended notification of legionellosis cases, as well as temperature (T) management (T Ͻ 25°C and T Ͼ 60°C) to prevent growth of L. pneumophila in premise plumbing systems (5). Following the large LD outbreak at a flower show in 1999 (6), measures for control of Legionella were incorporated in drinking water regulations, and investigations into the relationship between drinking water quality, biofilm formation potential (BFP), and the multiplication of Legionella pneumophila bacteria in tap water installations were conducted (7)(8)(9). The use of a model system, the boiler biofilm monitor (BBM), representing worst-case conditions (intermittent flow at 37°C), revealed that L. pneumophila can multiply at low biofilm concentrations (BfCs) due to its ability to proliferate within protozoan hosts consuming oligotrophic bacteria that grow on drinking water-exposed surfaces (9).…”
mentioning
confidence: 99%
“…However, with increasing bacterial cell numbers in the drinking water during distribution, (i) more biofilm on the inside of the pipes 5,6 , and (ii) a larger chance of elevated numbers of higher organisms such as aquatic sow bugs (e.g., Asellidae, 1-12 mm) and oligochaete worms 6 , a (iii) higher risk of occurrence of Aeromonas 5 , total coliforms 7 , Escherichia coli 8 , and opportunistic pathogens such as Pseudomonas sp. 9 and NTB mycobacteria 10 , as well as Legionella pneumophila 11 will occur in the network. Moreover, there is higher risk for consumer complaints (e.g., brown water, smell) and higher costs (e.g., corrosion, misreading of water meters).…”
Section: Introductionmentioning
confidence: 99%
“…The tearing of biofilms is dependent on materials, speed and type of water flow. In the water systems turbulent water discharged the biofilm and intensify the spread of bacteria in comparison to laminar, or stagnant water which does not stimulate the spread, but allows the unobstructed growth of biofilm [6,11,12] L. pneumophila bacteria is capable of surviving under high humidity conditions and a relatively large range of ambient temperature between 20˚C-50˚C; however, it survives even at temperatures below freezing, due its protection in the biofilm and amebas. In addition, its ability to survive is also associated with symbiotic and parasitic interactions with other microorganisms.…”
Section: Introductionmentioning
confidence: 99%